2013
DOI: 10.1016/j.aju.2013.08.013
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy of tamsulosin therapy after extracorporeal shock-wave lithotripsy for ureteric calculi: A prospective randomised, controlled study

Abstract: ObjectiveTo evaluate whether tamsulosin hydrochloride is effective as an adjunctive medical therapy to increase the effectiveness of extracorporeal shock-wave lithotripsy (ESWL) for treating ureteric stones, and minimises the use of analgesic drugs after the procedure.Patients and methodsTo treat single ureteric stones of 5–15 mm in diameter, 130 patients were treated with ESWL. After treatment, equal numbers of patients were randomly assigned to receive either the standard medical therapy alone (controls) or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 26 publications
(56 reference statements)
2
8
0
Order By: Relevance
“…This agent has been widely investigated to improve the success rate of SWL for ureteral stones, and proved to be an effective therapy [11,12]. Also, several clinical trials [13,14,15] have proposed the benefit of tamsulosin after SWL for renal stones.…”
Section: Introductionmentioning
confidence: 99%
“…This agent has been widely investigated to improve the success rate of SWL for ureteral stones, and proved to be an effective therapy [11,12]. Also, several clinical trials [13,14,15] have proposed the benefit of tamsulosin after SWL for renal stones.…”
Section: Introductionmentioning
confidence: 99%
“…In a study by Singh et al [15], Visual Analogue Scale pain score in the Tamsulosin group was 24.92 ± 7.57 and in the control group was 41.81 ± 17.24, and the difference was statistically significant (P = 0.00). Hassan Ismail Mohamed showed that the mean cumulative Diclofenac dose was 380 mg/patient in the Tamsulosin group and 750 mg/patient in the control group and the difference was statistically significant (P = 0.004) [16]. We compared the requirement of the mean number of analgesic tablets in our study and found that the difference was significant between Groups A and C. We conclude that the use of Tamsulosin with Deflazacort can reduce most distressing symptoms of colic and associated with the decrease in requirement of analgesics.…”
Section: Requirement Of Analgesicsmentioning
confidence: 96%
“…In the control group, there were 8 (12%) complications, 4 with severe ureteric colic with the requirement of hospitalization and auxiliary procedure and another 4 with progressive hydronephrosis with fever. In the Tamsulosin group, 4 (6%) patients had fever with progressive hydronephrosis [16]. Bhagat et al [11] concluded that Tamsulosin improved the outcome of steinstrasse.…”
Section: Complicationsmentioning
confidence: 98%
See 1 more Smart Citation
“…Several randomized controlled trials (RCTs) studying the SFRs in different types of pharmacological therapy after ESWL have been reported 8 – 33 . However, most of these studies were designed to compare the clearance rates between one medication and control 8 – 10 , 12 , 13 , 15 – 20 , 22 – 32 . Moreover, in most studies, an arbitrary endpoint time was set to assess the stone clearance rate while ignoring possible variations of therapeutic effect before and after that endpoint time 8 – 14 , 18 , 19 , 21 , 23 , 25 , 26 , 28 , 29 , 31 33 .…”
Section: Introductionmentioning
confidence: 99%